PENERAPAN TEKNOLOGI PENGOLAHAN IKAN ASAP PADA NELAYAN DI KELURAHAN HAMADI KOTA JAYAPURA - Kalvin Paiki; Ervina Indrayani; Lisiard Dimara; John D. Kalor (LPPM Uncen, 2019)
Fish fumigation is one method of fish processing that combines the process of salting, heating and adhering to the chemical components of smoke. Fish fumigation is intended for preservation, but this role has now shifted towards flavor formation, the distinctive color and aroma of smoked fish. Fishermen in Hamadi Village, Jayapura City have been doing of smoked fish for a long time, now it is a main business for every family. But so far the production of processed fish is mostly traditional processing, so it has not considered health and food safety factors such as negative impacts on the environment, as well as consumer concerns about carcinogenic compounds and air pollution. The Training of Technology Utilization use smoking cabinet as an alternative method of fish fuming, it is cheap and easy to apply and environmentally friendly. The methods was following, the observation, Interviews, Counseling and Training. Activities were carried out in July - August 2018. The results of the activities were obtained, 86% said they had never participated in the activity, while 14% had already followed. After the activities were carried out 57% said they were very satisfied, 43% said they were satisfied.Keywords: Smoking Cabinet, Fish, Society, Jayapura